Analisis Kinerja Keuangan Pada PT. Harum Energy Tbk Berdasarkan Rasio Likuiditas,Solvabilitas Dan Profitabilitas Periode 2020-2024 - Legina, Syiefa Fatria; Octovian, Reza (MASHLAHAH, 2025)
This research aims to analyze the financial performance of PT Harum Energy Tbk using financial ratios, namely liquidity ratio, solvency ratio, and profitability ratio during the period of 2020 to 2024. The data used in this research is sourced from the company’s officially published annual financial statements. The analysis method used is quantitative descriptive method. The results show that PT Harum Energy Tbk is in a healthy financial condition, with improved performance particularly in profitability ratios as a result of the surge in global coal prices in recent years.